Study on Characteristic of Bed Material and Bed Load Discharge in Sungai Jemberau, Tasik Chini due to Mining and Logging Activities - Nadiatul Adilah, Ahmad Abdul Ghani; N. Syamimi, Namin; Norashikin, A. Kamal; Junaidah, Ariffin (2017)
Tasik Chini is one of the two natural lakes in Peninsular Malaysia, which is located in the state of Pahang about 100 km from Kuantan, the capital of the state of Pahang. Based on the topographical map, most of the lowland within the study area has been converted into agricultural and including rubber and oil palm plantations and mixed crops. This logging and mining activities gave impact to sediment characteristics and discharge. The purpose of this study was to identify the bed material characteristics and to determine the bed load discharge in Sungai Jemberau at Tasik Chini. Bed material sample was collect at Sungai Jemberau in 24 November 2016, 1 December 2016 and 5 March 2017. Bed load results gave the variation of sediment transport modes in Sungai Jemberau cause by human activities nearby. The bed load discharges were estimated by using Duboys and Schoklitsch equation. From the analysis of the results, Duboys Equation was more suitable to predict and estimate the bed load discharges for Sungai Jemberau at Tasik Chini. This is because the equation is more suitable for uniform sediments with the specific gravity that are varying from 1.25 to 4. The particle size range for the Duboys equation is between 0.01–4.0mm.